The Financial Consequences for Both Partners: A Comparative Study - Kutsniashvili, Nino (European Scientific Journal, ESJ, 2025)
Of the many issues that arise when a marriage breaks down, none is more complex and important than the financial consequences of divorce, as these issues are also related to the rights of the child. This paper focuses on analyzing the economic consequences of divorce for both partners, focusing on the financial outcomes for men and women following marital dissolution. By examining key factors such as asset division and income disparities, the study provides a comprehensive view of how divorce impacts the long-term financial stability of both parties. The methodology of this study is purely comparative, serving as the foundation for the analysis. Utilizing a comparative approach, the paper specifically examines the divorce laws and their financial implications in Germany, Austria, England, Georgia, and France. This approach highlights variations in asset division, spousal support, and financial recovery across these countries, offering insights into how different legal systems address financial disparities between partners post-divorce. Across different legal systems and cultural contexts, the paper underscores disparities in financial recovery post-divorce and identifies systemic factors that influence these outcomes. The findings suggest that while both partners experience financial challenges, the degree and nature of these consequences vary significantly based on gender, legal frameworks, and individual financial circumstances. This analysis offers important insights into the economic dimensions of divorce and contributes to ongoing discussions on legal reforms and policy adjustments aimed at addressing these disparities.